Kitosan dari Limbah Kulit Kepiting Rajungan (Portunus sanginolentus L.) sebagai Adsorben Zat Warna Biru Metilena - Tanasale, Matheis F.J.D.P.; Killay, Amos; Laratmase, Marsela S (Jurnal Natur Indonesia, 2012)
The chitosan from shell of crabs (Portunus sanginolentus L.) waste was produced from deproteinization, demineralization, depigmentation,and deacetylation steps. This process was obtained 22.66% chitosan which identified by FTIR spectrophotometry and had 65.47% degree ofdeacetylation. This chitosan was used to adsorb methylene blue dye which fit to the Langmuir isotherm with 0.0312 l mg -1 equilibriumconstant of adsorption (K) and 4.20 mg g -1 maximum capacity of adsorption (q m).